Study of nasal packing versus quilting following septoplasty surgery - Sah, Kusheswar; Sigdel, Brihaspati; Nepali, Rajendra (Journal of Gandaki Medical College-Nepal, 2022)
Introduction: Nasal packing is a commonly performed procedure after septoplasty. Quilting is alternative procedure which reduces the complications of nasal packing. This study aims to compare the post-operative outcome of quilting and nasal packing following septoplasty. Methods: This is a prospective comparative study carried on 80 patients divided into two equal groups who had undergone quilting and nasal packing randomly after septoplasty surgery for symptomatic deviated nasal septum. Post-operative nasal outcome score, pain, haemorrhage, anxiety, infection was compared between two groups at 1st, 3rd, 7th and 30th post-operative days. Results: There was significant improvement in nasal obstruction post-operatively in quilting group (p<0.05). Polyvinyl acetate sponge nasal packing group patients experienced significantly higher intensity of pain on 1st and 3rd post-operative days (p<0.05). Post-operative bleeding was also relatively higher in nasal packing group compared to quilting group at 3rd post-operative day. Patients had significantly higher levels of anxiety in the nasal packing group throughout a week post-operatively compared to the quilting group. Similarly, no statistically significant difference was noted in terms of adhesion between group A and group B on 7th and 30th post-operative day. Conclusions: Quilting technique following septoplasty showed higher improvement of post-operative nasal obstruction compared to Polyvinyl acetate sponge packing. It also decreased post-operative pain, bleeding, anxiety and adhesion. Quilting suturing following septoplasty can be recommended as an effective and comfortable alternative to nasal packing.